Effect of Volume Fraction hybrid composite duck feathers (Anas Plathycus Borneo) - Rat Purun Fiber (Eleocharis Dulcis) With Matrix Polyester On Tensile And Bending Strength - Syarief, Akhmad; Fadliyanur; Suryanta, Dhanu; Nugraha, Andy; Aufa Ramadhasari, Aulia; Setiawan, Bayu (Fakultas Teknik Universitas Brawijaya, 2022)
Alabio ducks (Anas Plathycus Borneo) developed in the Alabio area of Hulu Sungai Utara Regency, South Kalimantan with a duck population in 2006 recorded at 3,487,002 heads. So far, alabio ducks have only been used for meat and eggs, even though the feather part of this one poultry can also be used as a composite raw material because of its relatively strong and elastic nature. To improve the quality of the composite, duck feathers are combined with rat purun fibers (eleocharis dulcis) so that they become Hybrid composites. Fraksi volume Hybrid composite Duck Feathers and Rat Purun Fiber are as follows 10% : 90 %, 20% : 80%, 30% : 70%, 40% : 60%, 50% : 50%, 60% : 40%, 70% : 30%, 80% : 20%, 90% : 10%. This study used experimental methods. From the results of the study, it is known that the value of tensile and tensile strength stress and bending strength decreased as the percentage of rat purun fibers decreased compared to the percentage of duck feathers.